Law nº 10.639/2003: the teaching-pedagogical use of anti-racist films for the decolonization of knowledge in science and mathematics teaching (Research, Society and Development, 2022)
In the historiography of Brazilian education since the colonial period at all levels, learning modalities, contexts, and educational documents, it represents the culture and socio-scientific knowledge of a Eurocentric, sexist, masculine, American and white-centric base, on the other hand, in the school curriculum there are erasures of scientific productions. produced by thinkers of African origin in school curricula. The objective of this research is to present the didactic use of anti-racist filmographies in teaching and learning in Science Education and Mathematics Education in Basic Education; basic education on knowledge of Science and Mathematics of African origin. The guiding question outlined: do filmographies with anti-racist themes have the potential to promote curricular decolonization in the teaching of Science and Mathematics? The methodological path designed consisted of a qualitative research in the Action Research procedures carried out in 2019; For data collection, semi-structured interviews with 96 students were used; Data analysis was engendered in the qualitative methodology of content analysis in association with discourse analysis. Among the main results, it was found that anti-racist films promoted students' contact with scientific production of African origin; It is verified that teaching Science and Mathematics teaching content through the didactic resource of anti-racist films promoted the effectiveness of Law n°10.639/2003. It is concluded that the use of anti-racist films has a potentializing action for the decolonization of the school curriculum in the aforementioned subjects, contributing significantly to the study and contact of students with the scientific knowledge produced by intellectuals of African origin.